A Dynamic Approach to Measuring China's Provincial Energy Supply Security along "the Belt and Road". (31st May 2018) - Li, Pin; Zhang, Jin-suo; Xu, Jian; Wang, Ping
Abstract : Using a dynamic model from 2005 to 2015, this study assessed China's energy supply security in the provinces along "the Belt and Road". Energy supply security was conceptualized across four dimensions: availability, affordability, acceptability, and energy technology and efficiency. A dynamic model was used to calculate the dynamic weights for each indicator and to examine the variation laws. It was found that the acceptability dimension indicator weights had rapidly increased, indicating that energy supply security had been widely accepted. Smooth weights were found for the availability dimension indicators, indicating that the resources needed to protect basic energy supplies were available. A synthetical energy supply security evaluation index was also analyzed for each "Belt and Road" province using a "quadratic weighting" method, which showed that the index was different in the same provinces in different years and different for different provinces in the same year. For 14 "Belt and Road" provinces, the overall energy supply security was found to have a "V" shape and a general dynamic upward trend, with the trends in the northwest and southeast provinces and along the whole "Belt and Road" found to be consistent. The energy supply security differences between these provinces were analyzed deeply in this paper; it will help us to understand the strengths and weaknesses of energy supply security levels in these provinces. The result will make it easier to cooperate with other provinces or countries along the "Belt and Road" in energy supply.